2018
DOI: 10.1101/455519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seizure-associated spreading depression is a major feature of ictal events in two animal models of chronic epilepsy

Abstract: Spreading depression is characterized by slow, propagating wave of cellular depolarization (SD) and is wildly associated with migraine, stroke, and traumatic brain injury. Seizures and spreading depression (or spreading depolarization, SD) have long been reported to coincide in acute seizure induction experiments. However, SD has not been observed associated with spotaneous seizures in animal or clinical recordings. Recently, advances in acquisition systems for neurointensive care units have made routine obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Profound shifts in extracellular concentrations of most if not all ions, elevated levels of numerous neurotransmitters and neuromodulators, metabolic and hemodynamic alterations, and morphological and gene expression changes, can all contribute to the antiseizure effect to some extent. It has been proposed that the concept of the ictus in epilepsy could be broadened to include a trajectory of seizures terminated by SD, seen in spontaneous epilepsy 7 and predicted by biophysics 9,10 . Given the overlapping cellular and electrophysiological mechanisms of seizures and SD, it is not easy to find an intervention that directly and selectively blocks SD occurrence without affecting the seizures to dissect the causality between these two phenomena and their mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Profound shifts in extracellular concentrations of most if not all ions, elevated levels of numerous neurotransmitters and neuromodulators, metabolic and hemodynamic alterations, and morphological and gene expression changes, can all contribute to the antiseizure effect to some extent. It has been proposed that the concept of the ictus in epilepsy could be broadened to include a trajectory of seizures terminated by SD, seen in spontaneous epilepsy 7 and predicted by biophysics 9,10 . Given the overlapping cellular and electrophysiological mechanisms of seizures and SD, it is not easy to find an intervention that directly and selectively blocks SD occurrence without affecting the seizures to dissect the causality between these two phenomena and their mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Both are also known to predispose to seizures. Moreover, seizures and SD share common triggers 1 , and seizures can culminate in SD both in experimental animals 6,7 and in humans 8 . Indeed, a mixed dynamic of seizure and SD is predicted by an extended Hodgkin-Huxley model incorporating cell volume changes and oxygen availability, suggesting that seizures and SD represent a dynamic continuum of neuronal membranes 9,10 .…”
mentioning
confidence: 99%
“…secondary brain insults following TBI (14,15). Although SDs are more prevalent than seizures in human recordings after brain injury (53% SD prevalence vs. ~15% seizure prevalence) (17,74,75), both have the potential to exacerbate tissue damage (13,25,26), and both occur together in animal models (19)(20)(21)(22)(23)(24) and in humans after TBI (17). Importantly, both SDs and seizures in patients with TBI are correlated with poorer clinical outcomes (14,27) and are being considered as measurable biomarkers of injury (76).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, SDs are observed immediately after injury, with electrophysiological depression lasting almost 3 hours after injury (18). SDs and seizures are also seen together in experimental preparations (19)(20)(21)(22)(23)(24). When either SDs or seizures occur in the injured brain, they impose a substantial metabolic burden that exacerbates tissue damage (13,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality in persons with epilepsy are nearly two times that of the population at large ( Thurman et al, 2017 ). In 2015, Aiba and Nobels demonstrated that spreading depolarization (SD) invading the brainstem could cause autonomic shutdown, and therefore might be one of the mechanisms of SUDEP ( Aiba and Noebels, 2015 ), and once looked for, spontaneous seizure-associated SD has been observed in animal models of epilepsy ( Ssentongo et al, 2017 ; Bahari et al, 2018 ; Loonen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%